An Analysis of The Professional Separation of Educators (Lecturers) and Political Party Participants in The Civil Servant in The 2024 Election - Taufiq Hidayat; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2024)
Political parties can be interpreted as a means for citizens to participate in the management of the state. Political parties are new organisations that have emerged in society, younger than existing organisations in society. Lecturers as state officials, namely the Civil servant (ASN) in their role as educators and as political party participa nts in elections must be able to balance their main duties as a lecturer. As regulated in Law Number 14 of 2005 which discusses teachers and lecturers who have the right to participate in political parties. However, many laws and regulations in Indonesia r egulate the prohibition of state officials to attend elections directly. This research uses one method, namely the juridical normative research method with a statutory approach and a conceptual approach, where the legal materials used are in the form of la ws and regulations as primary legal materials and books, legal journals as secondary legal materials, and other supporting sources through the internet in tertiary legal materials with qualitative descriptive legal material analysis techniques. Universitie s are at the forefront of creating citizens with academics and integrity. The 2024 election is a place to present prospective leaders who have integrity and quality. Lecturers as teaching staff have a role and contribution as parties who maintain the ethics and integrity of a nation's development. The role of universities in the context of elections that are in accordance with the principles of the elections themselves, of course the actors in universities, such as students and lecturers, are the main actor s to encourage this.